2008 International Wireless Communications and Mobile Computing Conference 2008
DOI: 10.1109/iwcmc.2008.115
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Frequency Reuse Planning for WiMAX over Frequency Selective Channels

Abstract: Fourth generation broadband wireless access systems based on OFDMA/OFDM techniques operate in pointto-multipoint (PMP) configuration so that conventional cellular planning methods can be used for network design. As an alternative planning method fractional frequency reuse (FFR) strategy has been recently proposed for OFDMA/OFDM cellular systems such as WiMAX. For what concerns the determination of the system outage prediction, planning procedures for multi-carrier systems are usually based on bit error rate cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…as in [6]- [8]) from those in [3] so that coverage requirements could be not guaranteed at all i.e. outage could be over the prescribed limits 1 and coverage holes could be present along the rail track.…”
Section: A Radio Coverage Issuesmentioning
confidence: 99%
“…as in [6]- [8]) from those in [3] so that coverage requirements could be not guaranteed at all i.e. outage could be over the prescribed limits 1 and coverage holes could be present along the rail track.…”
Section: A Radio Coverage Issuesmentioning
confidence: 99%
“…In [16], an analytic model for estimating the throughput of FFR is presented. The idea of using analytic models instead of simulation to assess the signal-to-interferenceand-noise ratio (SINR) for FFR is adopted also in [17]. In [18], it is shown that, if FFR is performed in a distributed fashion, and each cell selfishly optimizes the assignment of resource to its own users, the system will converge to a Nash equilibrium.…”
Section: Related Workmentioning
confidence: 99%
“…In References 9–11, FFR for Mobile WiMAX is considered, which suggests time division of the available total bandwidth with different FRFs, i.e., cell‐edge bandwidth with FRF of 3 and cell‐center bandwidth with FRF of 1. So, downlink subframe is split into two parts: one for cell‐center users, and the other for cell‐edge users.…”
Section: Introductionmentioning
confidence: 99%